Advances in the Physico-Chemical, Antimicrobial and Angiogenic Properties of Graphene-Oxide/Cellulose Nanocomposites for Wound Healing - Ugo D'Amora; Sawsan Dacrory; Mohamed Sayed Hasanin; Angela Longo; Alessandra Soriente; Samir Kamel; Maria Grazia Raucci; Luigi Ambrosio; Stefania Scialla (MDPI AG, 2023)
Graphene oxide (GO) and its reduced form (rGO) have recently attracted a fascinating interest due to their physico-chemical properties, which have opened up new and interesting opportunities in a wide range of biomedical applications, such as wound healing. It is worth noting that GO and rGO may offer a convenient access to its ready dispersion within various polymeric matrices (such as cellulose and its derivative forms), owing to their large surface area, based on a carbon skeleton with many functional groups (i.e., hydroxyl, carboxyl, epoxy bridge, and carbonyl moieties). This results in new synergic properties due to the presence of both components (GO or rGO and polymers), acting at different length-scales. Furthermore, they have shown efficient antimicrobial and angiogenic properties, mostly related to the intracellular formation of reactive oxygen species (ROS), which are advantageous in wound care management. For this reason, GO or rGO integration in cellulose-based matrixes have allowed for designing highly advanced multifunctional hybrid nanocomposites with tailored properties. The current review aims to discuss a potential relationship between structural and physico-chemical properties (i.e., size, edge density, surface chemistry, hydrophilicity) of the nanocomposites with antimicrobials and angiogenic mechanisms that synergically influence the wound healing phenomenon, by paying particular attention to recent findings of GO or rGO/cellulose nanocomposites. Accordingly, after providing a general overview of cellulose and its derivatives, the production methods used for GO and rGO synthesis, the mechanisms that guide antimicrobial and angiogenic processes of tissue repair, as well as the most recent and remarkable outcomes on GO/cellulose scaffolds in wound healing applications, will be presented.